Análise da conversação e teoria da polidez empregadas nas soluções consensuais de litígios: mediação e conciliação - Araujo, Claudia Poliana de Escobar de (2021)
This work aims to investigate, within a social-interactional perspective of the spoken language, the difficulties in the use of language in consensual conflict resolution hearings: mediation and conciliation. The theoretical framework is mainly based on the principles of Conversation Analysis, Forensic Linguistics, Politeness, Facework, Pragmatics and Argumentation. Concerning the development of this work, mediation techniques were considered as analysis parameters, as well as the use of linguistic and paralinguistics strategies for the application of these techniques. The corpus is composed of the following procedures: in order to collect qualitative data, we initially use interviews with mediators to survey the research problem. Then, we developed an Undergraduate Teaching Project that collaborated as a laboratory for the next steps of data collection in this research. Thus, we also obtained natural data from the reality observed in real mediation hearings, which resulted in the production of material for training mediators (E-book); natural data from the teaching project – transcripts according to Preti (2003), from the simulated hearings and from feedback regarding the effectiveness of the intervention by means of the E-book and linguistic training; quantitative data collected by means of an online form, answered by the participants of the Undergraduate Teaching Project. Due to our involvement and linguistic intervention in the legal field in the context of mediation and conciliation hearings, the methodology has an applied nature that can be considered as field research and action research. According to the findings, we observed that the proposal for linguistic intervention – E-book and linguistic training – contributed a great deal to the progress of the simulated hearings in which they were tested. We also highlight that the mediation techniques that showed the most significant changes were: Validation of Feelings, Recontextualization and Organization of Interests and Feelings. These data revealed the importance of the linguist with professionals who depend on communication for the accomplishment of their work, especially in the legal environment, which was our context of studies.